CHARACTERISTICS OF HABITAT, DISTRIBUTION, AND DIVERSITY OF ANOPHELES SPP IN KEMELAK BINDUNG LANGIT VILLAGE, OGAN KOMERING ULU REGENCY, SOUTH SUMATRA - Maretasari, Giri; Windusari, Yuanita; Lamin, Syafrina; Hanum, Laila; Septiawati, Dwi (Journal of Environmental Science and Sustainable Development, 2019)
Malaria is an infectious disease caused by Plasmodium andis transmitted through the bite of a female Anopheles vector. Ogan Komering Ulu (OKU) is a district in South Sumatra that is endemic to malaria. The study aims to determine habitat type, environmental factors that influence larvae development, and distribution of Anopheles larvae. The experiment was conducted from January to February 2019 in the Kelurahan Kemelak Bindung Langit, OKU. Species identification was carried out in the Entomology Laboratory, Baturaja Health Research and Development Center, OKU. Sampling locations were determined based on field observations, through simple purposive sampling. Identification of mosquito larvae which were maintained in the laboratory, showed that they originated from four Anopheles species namely An. vagus, An. barbirostris, An. kochi, and male Anopheles. The dominant habitat (76,89%) was rice fields. The characteristics of larval breeding habitats included water pH of 5-6, water temperature of 280C-320C, light intensity of 756 - 761 mmHg, visual clear water, muddy substrates, and habitat distance with houses of 10 -60 m. The Anopheles type diversity index (H ') was low (0.04-0.36). The larval density was the highest in RT 1 and RT 2 (as many as 2.5 larvae/cauldrons), and the lowest in RW 3 locations (as many as 0.1 larvae/cauldron), which had the same habitat type, namely, rice fields. The highest dominance index (C) was found in male Anopheles (C = 1), and the lowest was detected in An. kochi (C = 0.02) and An. barbirostris (C = 0.01). The pattern of the spread of Anopheles based on the Morishita index was grouped (Id> 1) and uniform (Id <1).